Accurate diagnosis of bullous pemphigoid requires multiple health care visits - Leisti, Päivi; Pankakoski, Anna; Jokelainen, Jari; Varpuluoma, Outi; Huilaja, Laura; Panelius, Jaana; Tasanen, Kaisa (Frontiers in Immunology, 2023)
Accurate use of diagnostic codes is crucial for epidemiological and genetic research based on electronic health record (EHR) data. This retrospective study validated the International Classification of Diseases (ICD)-10 diagnostic code L12.0 for bullous pemphigoid (BP) using EHR data from two Finnish university hospitals. We found 1225 subjects with at least one EHR entry of L12.0 between 2009 and 2019. BP diagnosis was based on clinical findings characteristic of BP and positive findings on direct immunofluorescence (DIF), BP180-NC16A enzyme-linked immunosorbent assay (ELISA) or indirect immunofluorescence (IIF) assay. True BP was found in 901 patients; the positive predictive value (PPV) for L12.0 was 73.6% (95% CI 71.0-76.0). L12.0 was more accurately registered in dermatology units than any specialized health care units (p<0.001). Including patients with multiple L12.0 registrations (≥3), increased the accuracy of the L12.0 code in both dermatology units and other settings. One diagnostic code of L12.0 is not enough to recognize BP in a large epidemiological data set; including only L12.0 registered in dermatology units and excluding cases with <3 L12.0 record entries markedly increases the PPV of BP diagnosis.